Pediatric Airway Management and Prehospital Patient Safety: Results of a National Delphi Survey by the Children's Safety Initiative-Emergency Medical Services for Children. Issue 9 (September 2016) - Hansen, Matthew; Meckler, Garth; O'Brien, Kerth; Engle, Phillip; Dickinson, Caitlin; Dickinson, Kathryn; Jui, Jonathan; Lambert, William; Cottrell, Erika; Guise, Jeanne-Marie
Abstract : Objective: The objective of this study was to determine what aspects of prehospital pediatric airway management may contribute to patient safety events. Methods: We conducted a 3-phase Delphi survey in prehospital professionals across the United States to identify potential contributors to patient safety events. Respondents ranked how likely factors were to contribute on a 9-point Likert-type scale and were allowed to elaborate through open-ended questions. Analysis was conducted using a mixed-methods approach, including Likert-type responses and open-ended questions which were analyzed for specific themes. Results: All 3 phases of the survey were completed by 492 participants; 50.8% of respondents were paramedics, 22% were emergency medical technician-basics/first responders, and 11.4% were physicians. Seventy-five percent identified lack of experience with advanced airway management, and 44% identified medical decision making regarding airway interventions as highly likely to lead to safety events. Within the domain of technical skills, advanced airway management was ranked in the top 3 contributors to safety events by 71% of participants, and bag-mask ventilation by 18%. Qualitative analysis of questions within the domains of equipment and technical skills identified endotracheal intubation as the top contributor to safety events, with bag-mask ventilation second. In the domains of assessment and decision making, respiratory assessment and knowing when to perform an advanced airway were ranked most highly. Conclusions: This national Delphi survey identified lack of experience with pediatric airway management and challenges in decision making in advanced airway management as high risk for safety events, with endotracheal intubation as the most likely of these.